(untitled) (Genius Repository, 2023)
In the conditions of market relations, the content of property rights changes, the expansion of the range of property objects makes it possible to achieve economic stability of the country. New modern approaches appear in this field. Legal basis will be created. There is a need for a new legal consciousness and legal thinking. This article discusses the concept of intellectual property, its essence, practical importance, and its role in the economic development of society.